Contrasting biogeochemical characteristics of the Oubangui River and tributaries (Congo River basin) - Bouillon, Steven (Nature Publishing Group, 2014)
The Oubangui is a major tributary of the Congo River. We describe the biogeochemistry of contrasting tributaries within its central catchment, with watershed vegetation ranging from wooded savannahs to humid rainforest. Compared to a 2-year monitoring record on the mainstem Oubangui, these tributaries show a wide range of biogeochemical signatures, from highly diluted blackwaters (low turbidity, pH, conductivity, and total alkalinity) in rainforests to those more typical for savannah systems. Spectral analyses of chromophoric dissolved organic matter showed wide temporal variations in the Oubangui compared to spatio-temporal variations in the tributaries, and confirm that different pools of dissolved organic carbon are mobilized during different hydrological stages. δ(13)C of dissolved inorganic carbon ranged between −28.1‰ and −5.8‰, and was strongly correlated to both partial pressure of CO(2) and to the estimated contribution of carbonate weathering to total alkalinity, suggesting an important control of the weathering regime on CO(2) fluxes. All tributaries were oversaturated in dissolved greenhouse gases (CH(4), N(2)O, CO(2)), with highest levels in rivers draining rainforest. The high diversity observed underscores the importance of sampling that covers the variability in subcatchment characteristics, to improve our understanding of biogeochemical cycling in the Congo Basin.